2008
DOI: 10.1152/ajpheart.01137.2007
|View full text |Cite
|
Sign up to set email alerts
|

The neurovascular dysfunction induced by angiotensin II in the mouse neocortex is sexually dimorphic

Abstract: Women are less susceptible to the cerebrovascular complications of hypertension, such as a stroke and vascular dementia. The mechanism of such protection may be related to a reduced vulnerability of women to the cerebrovascular actions of hypertension. To test this hypothesis, we used a model of hypertension based on infusion of angiotensin II (ANG II), an octapeptide that plays a key role in hypertension and produces cerebrovascular dysregulation. Cerebral blood flow (CBF) was monitored by laser-Doppler flowm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 44 publications
(75 reference statements)
7
45
1
Order By: Relevance
“…12 Furthermore, our findings are conceptually consistent with a recent study reporting that AngII administration attenuates the increase in cerebral blood flow induced by the endothelium-dependent vasodilator, acetylcholine, or whisker stimulation in male, but not female mice. 13 To test for a role for Nox2-containing NADPH-oxidases in the gender differences in cerebrovascular responses to AngII we studied Nox2-deficient mice. Firstly, we measured AngIIstimulated O 2 Ϫ production by cerebral arteries from WT and …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Furthermore, our findings are conceptually consistent with a recent study reporting that AngII administration attenuates the increase in cerebral blood flow induced by the endothelium-dependent vasodilator, acetylcholine, or whisker stimulation in male, but not female mice. 13 To test for a role for Nox2-containing NADPH-oxidases in the gender differences in cerebrovascular responses to AngII we studied Nox2-deficient mice. Firstly, we measured AngIIstimulated O 2 Ϫ production by cerebral arteries from WT and …”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, studies have reported a marked gender difference in the effects of AngII on mouse cerebral arteries. 12,13 However, the role of NADPHoxidase in such gender differences has not been evaluated. Therefore, we first tested whether gender influences the levels of ROS generated in cerebral arteries in response to AngII, and then whether contractile responses to AngII were similarly gender-dependent.…”
mentioning
confidence: 99%
“…Regional CBF was measured during the MCAO surgery as described previously (6,14). Briefly, an incision was made in the scalp to expose the skull.…”
Section: Methodsmentioning
confidence: 99%
“…Under the age of 45 yr, fewer women than men die from cardiovascular disease (1), a pattern which is reversed after menopause (52). Similar sex-associated differences exist in animal hypertension models: females develop hypertension later, and less severely, than males (11,35,62). Studies in humans and animal models indicate that central nervous system pathways play a critical role in the development and maintenance of hypertension (27).…”
mentioning
confidence: 90%